Garis dan Titik Berdasarkan Riset Visual - Devi Kurniawati Homan (Humaniora, 2015)
A design may not be created instantly, without going through a process of creation. At the beginning it all starts from nothing, blank. It requires a visual research to make a visual communication. Without a visual research, the design will not have a strong meaning to be communicated. When an idea is created, the next step is to generate the idea to become a design. The first thing a designer to do is drawing a line. Line is one of the design basic elements. In the journey to make a good design, a designer requires a visual record to assist her/him in remembering what is important. A visual record contains not only visual things seen by eyes, but also the perceived things. What is felt at the moment is important because it is easier to forget than visual memory. Sense is an important element in design. A good work will easily be communicated not only by visuals but also from senses. The study was conducted as an insight into the process of making a visual record of nirmana using visual recording method in the exploration of dots and dashes. This method was used to sharpen the sensitivity of students to dots and lines. Initially, the students visited a traditional market to do the visual research. After that, they created a visual record in the form of the composition of dots and lines in nirmana to remember the taste, smell, and visual experiences.